2017
DOI: 10.1097/pec.0000000000001283
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Could Streamline the Emergency Department Workflow of Clinically Nonspecific Intussusception

Abstract: Objectives The aim of this study was to evaluate whether point-of-care ultrasound (POCUS) for intussusception screening streamlines the workflow of clinically nonspecific intussusception (CNI), an intussusception presenting with only 1 manifestation of the classic triad, and/or vomiting. Methods We reviewed 274 consecutive children with intussusception, aged 6 years or younger, who visited a tertiary care hospital emergency department between May 2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…In fact, one study found that the institution of a POCUS protocol for intussusception reduced length of stay by over 200 minutes and shortened the door-to-reduction time by 26 minutes. 24 A recent systematic review and meta-analysis by Tsou et al 23 evaluated combined radiologic ultrasound and POCUS, demonstrating similar sensitivity and specificity to our study. However, our study differs in that we excluded radiology ultrasound and focused specifically on POCUS for intussusception.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, one study found that the institution of a POCUS protocol for intussusception reduced length of stay by over 200 minutes and shortened the door-to-reduction time by 26 minutes. 24 A recent systematic review and meta-analysis by Tsou et al 23 evaluated combined radiologic ultrasound and POCUS, demonstrating similar sensitivity and specificity to our study. However, our study differs in that we excluded radiology ultrasound and focused specifically on POCUS for intussusception.…”
Section: Discussionsupporting
confidence: 86%
“…POCUS reduces patient length of stay in the emergency department [38]. While exact numbers vary across emergency departments, reduction in length of stay ranged from 26 minutes to two hours [39,40]. This reduction in the length of stay is most significant during evening, overnight, and weekend visits [38,41].…”
Section: The Future Of Ultrasoundmentioning
confidence: 99%
“…In contrast, ultrasound can accurately diagnose intussusception with a high accuracy of 97.9% sensitivity and 97.8% specificity, and therefore is recommended as the diagnostic modality of choice [7]. However, requesting radiologist-performed ultrasound (RADUS) in all clinically suspected cases might be time-consuming and inefficient for the ED workflow [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that point-of-care ultrasound (POCUS) performed by pediatric emergency physicians could be a practical measure [8][9][10]. POCUS for detecting intussusception is relatively easy to learn and readily available in the ED [10][11][12].…”
Section: Introductionmentioning
confidence: 99%